ANALISIS PENDAPATAN USAHATANI KOPI ARABICA (Coffea arabica) DI KECAMATAN SUMBERMANJING WETAN KABUPATEN MALANG - Basit, Basit; Purwatiningsih, Rini (grafting, 2023)
This study is intended to determine the income of farmers (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency, and the level of efficiency or feasibility of arabica coffee farming (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency.The analysis method used is farm income analysis and farm efficiency/feasibility analysis. The number of samples in this study was 25 people who were arabica coffee farmers (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency. Data collection using questionnaire method as primary data source and literature related to research. The results of the analysis show that (1) The income of Arabica Coffee Farming (Coffea arabica) in Sumbermanjing District, Malang Regency which is the result of a reduction between the total average revenue (TR) and the total average production cost (TC) of Rp 18.136.800,-. This means that the first hypothesis in this study is true, namely arabica coffee farming (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency, profitable; (2) The R/C ratio of arabica coffee farming (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency is 2,82. Based on the R/C ratio criteria, if the R/C ratio value is more than 1, then the farm is eligible for farming. So, in accordance with these criteria, it can be known that arabica coffee farming (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency is feasible for farming. This means that the second hypothesis in this study is correct, namely usahatani arabica coffee (Coffea arabica) in Sumbermanjing Wetan District, Malang Regency is worth farming.